Ketika Rumah Tak Lagi Sama: Pergulatan Psikologis Tiga Anak dalam Bayang-Bayang Perceraian - Endy Alvinal Khoiri; Muhammad Hisyam Luqoni Avivi; Ani Qotuz zuhro’ Fitriana (Universitas Maritim AMNI Semarang, 2025)
Parental divorce causes the child to lose the love and affection of his parents and hinders them in their psychological development. This study describes and analyzes the psychological struggles experienced by three children who lost their father's role after divorce. All three experience similar inner conflicts: feelings of loss, neglect, and emotional division, as well as confusion in choosing to live with their father or mother. This study uses a qualitative case study approach and uses participatory observation and in-depth interviews for data collection. The results showed that children experienced conflicts about loyalty, emotional stress, and difficulty in reshaping their self-identity in a changing family environment. Children's mental and social instability is exacerbated by the loss of the father figure both physically and emotionally. The study emphasizes how important it is for parents to remain actively involved with their child even after they have divorced to maintain their emotional stability and provide ongoing psychological support. These findings are expected to be a reference for education practitioners, counselors, and parents in dealing with the psychological impact of divorce on children.